Broadband Antenna for LTE Operation: A Novel Design Approach Using Meandered Strip Line - M. Kumaran (Institute of Advanced Engineering and Science, 2015)
The broadband performance of an antenna for the LTE operation is presented in this paper. A novel design approach used to design the antenna using meandered strip line can be treated as a simplest and a cost effective approach. Due to the requirement of the bandwidth hungry applications, there is a smooth migration of the mobile technology from the existing services like GSM; UMTS to LTE is in progress. Thus a compact radiating structure can be preferred in many applications to improve the throughput performance of the multimedia service. The proposed antenna operates in the LTE 42 band. It shows the broadband performance centred at 3533 MHz with 112 MHz bandwidth. Bandwidth performance at this frequency is also found to be well suited to operate in the downlink frequency band at LTE 22. To determine the optimal performance of the antenna, a suitable threshold (S11 < 10 dB) is imposed. Gain and directivity of the antenna are 6.6 dB and 7.8 dBi respectively. Efficiency is achieved to 74%. Radiation pattern shows the best performance of the antenna. With the best performance achieved at this frequency, the antenna is advantageous to exploit in small cell coverage, LTE Hotspot and Indoor enhancement solutions. CST Microwave Studio Suite software is used to design the antenna. An ordinary 50 Ω transmission line is fed to the antenna. Other antenana parameters are also discussed for its performance.